LINEAR QUADRATIC REGULATOR APPLIED TO A MAGNETORHEOLOGICAL DAMPER AIMING ATTENUATE VIBRATION IN AN AUTOMOTIVE SUSPENSION - Roefero, L. G.P. [UNESP]; Chavarette, F. R. [UNESP]; Mishra, L. N. (My University, 2022)
Automotive suspension is a mechanical device used in automobiles to attenuate vibrations, which are caused by the undulation of the oor. This device can be modeled by a mass-spring-damper system, and the damper used in most real situations is a viscous medium damper, which dissipates energy passively. In this work, a 1=4 model of automotive suspension was analyzed when the passive shock absorber is exchanged for a magnetorheological shock absorber, whose control current is determined by a law of Optimal Linear Control. Based on the analyzes made in terms of displacement and acceleration, more satisfactory results were obtained in the system containing the AMR, in contrast to the results obtained with the presence of the passive damper.
Keywords: Automotive suspension; Lqr control; Magnetorheological damper; Vibration.